GREEN SYNTHESIS AND CHARACTERIZATION OF AG/MGO NANOCOMPOSITE AS ACTIVE COMPOUND FOR FREE-ANTIBIOTICS WOUND DRESSING - Alfajri Hikmattullah, Muhammad
The use of antibiotics in wound management can cause allergic reactions in some patients. The need for rapid wound treatment has driven the search for alternative methods that avoid allergic reactions while still preventing bacterial infections. Silver nanoparticles (Ag) are known for their effective antibacterial properties that reduce bacterial activity and have been widely applied in the medical field. However, continuous exposure of body cells to silver nanoparticles has been identified to cause toxic reactions, particularly in the dermis layer of the skin. In addition to silver, magnesium oxide (MgO) also has antibacterial properties, though with lesser effectiveness, and is not sufficient to prevent infections in wounds on its own. Ag/MgO nanocomposites are expected to reduce the toxicity of silver nanoparticles and enhance the antibacterial ability of MgO. This results in antibacterial properties that can be safely used on wounds without the risk of causing cell damage around the wound. Furthermore, MgO has been reported to accelerate wound closure. This study aims to synthesize Ag/MgO nanocomposites through green synthesis using palm leaf extract (Elaeis guineensis), which is rich in organic compounds such as flavonoids and phenolics that can play a role in reducing metal nanoparticles. The surface plasmon resonance characteristic of Ag nanoparticles at a maximum absorption wavelength of around 440 nm was identified and analyzed using UV-Vis spectrophotometry, while the crystal phase characterization of the nanocomposite was performed using powder X-ray diffraction (PXRD), revealing overlapping phases of Ag and MgO at 2? = 38.12°; 44.28°; and 64.42°. The morphology and atomic ratio of the nanocomposite were scanned using scanning electron microscopy equipped with energy dispersive spectroscopy (SEM-EDS), showing that the nanocomposite had a flake-like shape with thickness in the nano range and an atomic ratio of 3:5 Ag/Mg. The antibacterial properties of the nanocomposite were tested in vitro using the disk diffusion method against Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative) bacteria, demonstrating that the antibacterial properties of the Ag/MgO nanocomposite increased with the addition of silver precursor concentration during synthesis. The Ag/MgO nanocomposite exhibited stronger antibacterial properties than MgO and weaker than silver nanoparticles, indicating that the Ag/MgO nanocomposite is safer to use than silver nanoparticles as an active agent in preventing bacterial growth in wounds.